2014
DOI: 10.1063/1.4898806
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced amorphization of a dense coordination polymer and its impact on proton conductivity

Abstract: The proton conductivity of a dense coordination polymer (CP) was investigated under high-pressure conditions. Impedance measurements under high pressures revealed that the proton conductivity of the CP decreased more than 1000-fold at pressures of 3–7 GPa and that the activation energy for proton conduction almost doubled compared with that at ambient pressure. A synchrotron X-ray study under high pressure identified the amorphization process of the CP during compression, which rationally explains the decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The pressure induced amorphization of Zn­(HPO 4 )­(H 2 PO 4 ) 2 ·(H 2 Im) 2 and its effect on proton conductivity were investigated by Umeyama and coworkers in 2014 . In general, it is noteworthy that the preparation of sample contact for the measurement of the pressure-induced proton conductivity is notoriously challenging.…”
Section: Design and Strategies For Improving Proton Conductivity In M...mentioning
confidence: 99%
“…The pressure induced amorphization of Zn­(HPO 4 )­(H 2 PO 4 ) 2 ·(H 2 Im) 2 and its effect on proton conductivity were investigated by Umeyama and coworkers in 2014 . In general, it is noteworthy that the preparation of sample contact for the measurement of the pressure-induced proton conductivity is notoriously challenging.…”
Section: Design and Strategies For Improving Proton Conductivity In M...mentioning
confidence: 99%
“…2 Still, a limited number of glasses of CPs have shown potential applications for molecule trapping and conservation 3 and for ion transport in energy devices. 4 Today, all the glass CPs reported in the literature are obtained via a two-step route that requires the synthesis of a crystalline CP, followed by ball milling and pressurization, 5 heating or melt quenching 6 of the crystalline phase. 1b Most of the melt quenching approaches require the use of high temperature (between 400 and 600 C) in the case of zeolitic imidazolate frameworks (ZIFs).…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure crystallographic experiments over the last 25 years or so have proved to be a unique tool in probing the mechanical properties of the organic solid state, 1 metalcomplexes, and 2D/3D coordination compounds. 2 In particular, high-pressure techniques have been used to study an array of mechanical and chemical properties of crystals, such as changes in electrical and thermal conductivity, 3 pressureinduced melting, 4 solubility, 5 amorphisation, 6 post-synthetic modication, 7 and chemical reactions such as polymerisation, 8 cycloaddition 9 and nanoparticle formation. 10 Previous high-pressure experiments on porous metal-organic framework (MOF) materials have shown that on loading a diamond anvil cell (DAC) with a single-crystal or polycrystalline powder, the hydrostatic medium that surrounds the sample (to ensure hydrostatic conditions) can be forced inside the pores on increasing pressure, causing the pore and sample volume to increase with applied pressure.…”
mentioning
confidence: 99%